Modernizing NATO’s Nuclear Weapons - Ramsbotham, Oliver. author. aut Link
XX, 257 p. 2 illus.
Keywords: An examination of the current state of nuclear forces which explores the official defence policies of all 16 NATO countries, the rationale behind modernization plans and the opposition to these plans. The author establishes principles to guide continuing controversy in this area.